2013
DOI: 10.1002/ejoc.201300207
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tweezers with Freely Rotating Linker and Porphyrin Moieties

Abstract: Molecular tweezers were synthesised by using a microwave accelerated alkene plus cyclobutane epoxide reaction between norbornyl appended porphyrin moieties and a diepoxide functionalised phenyl diimide spacer. The tweezers contain several rotational degrees of freedom; about the porphyrin with respect to the norbornyl linker, and between the two norbornyl backbone sections. The ability of ZnII metallated tweezer 1 to complex 1,4‐diazabicyclo[2.2.2]octane (DABCO) was studied by UV/Vis and 1H NMR spectroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 73 publications
2
22
0
Order By: Relevance
“…11 In a series of bis-porphyrin hosts each containing different linker structures, [12][13][14] it has been observed that large association constants can be obtained for architectures containing either conformationally flexible, restricted, or more rigidly constrained linkers, and that the linker need only confer the system with moderate preorganization. § Additional evidence for this is provided by both our recent work 15 and a variety of porphyrin host-guest systems with varying degrees of preorganisation, [6][7][8]12,13,[16][17][18][19][20][21][22][23][24][25][26][27] including those which allow defined changes in interporphyrin distance. Further, there continues to be an active interest to explore linker conformational rigidity/flexibility in porphyrin tweezers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In a series of bis-porphyrin hosts each containing different linker structures, [12][13][14] it has been observed that large association constants can be obtained for architectures containing either conformationally flexible, restricted, or more rigidly constrained linkers, and that the linker need only confer the system with moderate preorganization. § Additional evidence for this is provided by both our recent work 15 and a variety of porphyrin host-guest systems with varying degrees of preorganisation, [6][7][8]12,13,[16][17][18][19][20][21][22][23][24][25][26][27] including those which allow defined changes in interporphyrin distance. Further, there continues to be an active interest to explore linker conformational rigidity/flexibility in porphyrin tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 This has led to discussion that adopting a rigid-only approach to host design which relies solely on covalent linkages to establish geometry could limit the scope of artificial receptors. 5,9 We have previously described the host-guest chemistry of bis-porphyrin tweezer 1, 15 which forms a strong 1•DABCO bis-porphyrin:DABCO complex with the aliphatic diamino ligand 1,4-diazabicyclo[2.2.2]octane (DABCO), and more recently reported the synthesis of a tetra-porphyrin tweezer 2 with two cooperative binding sites 30 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the results for the 1:2 plus 2:2 plus 1:4 complexation model. We were unable to compare this theoretical speciation with the experimental data as we have done previously since the ratio of the two sandwich species cannot be determined by integration of the free and sandwich porphyrin β‐pyrrole resonances. The sandwich porphyrin β‐pyrrole resonances appear at the same chemical shift for both the major 1:2 sandwich species and the minor sandwich species (which could be either 1:1 or 2:2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is evident that the complexation model is different between UV/Vis and NMR concentrations for the tetra‐porphyrin system 2 with DABCO. In this case, the UV/Vis titration data cannot be used to predict the behaviour of the system at higher concentrations in NMR, as has been previously applied to both ours and other systems. The alternate 1:2 plus 1:4 complexation model (see Supporting Information, section S8) only involves a single sandwich complex, and thus cannot explain the experimental speciation observed at NMR concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Highly pre-organised, fused [n]polynorbornane frameworks have been used in a number of supramolecular settings [32][33][34][35][36][37][38][39][40] and hosts such as 1 (Fig. 1) are well suited for study by NMR techniques as they are symmetric (C 2V and s), and their binding behaviour with a range of guest anions in solution has been studied in depth.…”
Section: Introductionmentioning
confidence: 99%